Three-Step Excision: An Easy Way for Composite Labia Minora and Lateral Clitoral Hood Reduction. Issue 6 (December 2021) - Xia, Zenan; Liu, Chang-Yi; Yu, Nanze; Liu, Zhifei; Zeng, Ang; Zhang, Yuwei; Si, Loubin; Long, Fei; Zhu, Lin; Wang, Xiaojun
Abstract : Background: Hypertrophy of the labia minora with lateral clitoral hood redundancy is common, but the excess clitoral hood is often overlooked during labiaplasty, which may result in imbalanced and unsatisfactory outcomes. The purpose of this study was to present an easy method of three-step excision for composite labia minora and lateral clitoral hood reduction. Methods: The procedure was performed in three steps: the prominent clitoral hood skin parallel to the labia majora and the clitoral hood sulcus was removed first; then, the protuberant portion of the labia minora was removed by wedge resection; and finally, a triangle at the junction between the labia minora and the clitoral hood was trimmed. Patients were required to return for examination on the first day and within 14 days after surgery. Follow-ups were arranged on the Internet or at the outpatient clinic. Satisfaction questionnaires were completed during follow-up. Results: Between January of 2016 and January of 2020, 136 patients underwent composite labia minora and lateral clitoral hood reduction. Ages ranged from 9 to 55 years. Six patients experienced complications (4.4 percent) and five underwent revision surgery (3.7 percent). The overall satisfaction rate within 14 days and after 3 months following surgery was 91.0 percent and 95.5 percent, respectively. Preoperative discomfort was resolved in 43.0 percent and significantly relieved in 54.2 percent, and sex life was improved in 70.9 percent. Conclusions: Three-step excision is effective and safe for composite labia minora and lateral clitoral hood reduction with very high satisfaction. Considering the advantages of easy preoperative design and controllable tissue removal, this method could be a better alternative to the present procedures. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.